Respon Guru dan Peserta Didik Terhadap Pembelajaran Fisika dengan Model Inkuiri Terbimbing Dipadu Advance Organizer - Mahesti Kusdiastuti; Ahmad Harjono; Gunawan Gunawan; Mir'atun Nisyah (Department of Physics Education, Universitas Mataram, 2019)
This study aims to determine the response of teachers and students to physics learning with a guided inquiry learning model combined with an advanced organizer. This research was conducted in three senior high schools in Mataram. This research is a pre-experimental study. The subjects of this study were 3 physics teachers and 60 students in Mataram. The data obtained in this study are teacher and studentÃ¢â¬â¢ questionnaire response data. The results of the study showed that both the response of students and the response to learning with guided inquiry learning models combined with advanced organizers included in the excellent category.